A Construção das Mentalidades Fixa e de Crescimento em Futuros Professores de Matemática: Uma Análise Narrativa das Experiências de Aprendizagem - (:unkn) unknown (Universidade Federal do Pampa, 2026)
This study investigated how the school experiences lived by undergraduate students in the Mathematics Teacher Education program at the Federal University of Pampa (Bagé Campus) influenced the development of fixed and growth mindsets, concepts developed by Carol Dweck and further explored by Jo Boaler in the field of Mathematics Education. Through a qualitative approach and the use of narrative inquiry, individual accounts were produced by students who, upon revisiting their trajectories with mathematics during basic education, revealed deep marks of success, failure, support, and abandonment. The narratives made it possible to understand how these experiences shaped the way the participants perceive themselves as learners and future teachers. The analysis was carried out based on thematic blocks that highlighted elements such as the impact of failure, the teacher's role, the family context, and other subjective issues that cross teacher education. The results indicate that mathematical mindsets are not fixed traits of individuals, but rather ongoing constructions influenced by the school environment, personal relationships, and the discourses surrounding mathematics education. The study emphasized the importance of training teachers capable of recognizing error as part of the learning process and the multiple ways in which prior school experiences influenced the development of future mathematics teachers’ mindsets. The narratives revealed the weight of emotions, relationships, and discourses in teacher education, highlighting the role of error and the school context in this process. The importance of sensitive listening and valuing individual trajectories was acknowledged. These understandings reinforced the need to train teachers who are more empathetic, critical, and open to growth.
Keywords: Mentalidade de crescimento; Mentalidade fixa; Educação matemática; Pesquisa narrativa; Formação docente; Growth mindset; Fixed mindset; Mathematics education; Narrative inquiry; Teacher education; CIENCIAS EXATAS E DA TERRA